Bubbles in trouble eaudiobook Bubbles yablonsky series, book 2. - Strohmeyer, Sarah (Bubbles Yablonsky, 2003)
Bubbles Yablonsky is in trouble. Her exposé of corruption in Lehigh's social heights has infuriated the local paper's editor, so she's still a fulltime hairdresser and only an occasional reporter. Her freeloading ex is back on her sofa after his socialite wife threw him out, her daughter's in love, and her mother thinks she's Jackie Onassis. Plus, Bubbles' chastity vow is not yet broken, which means sexy photographer Steve Stiletto's heart has remained just out of reach ... "Strohmeyer successfully navigates the fine line between humorous stereotype and sympathetic amateur investigator."— Publishers Weekly